2007
DOI: 10.1530/rep-07-0119
|View full text |Cite
|
Sign up to set email alerts
|

Actions of anti-Müllerian hormone on the ovarian transcriptome to inhibit primordial to primary follicle transition

Abstract: The oocytes found within the primordial follicles of mammalian ovaries remain quiescent for months to years until they receive the appropriate signals to undergo the primordial to primary follicle transition and initiate folliculogenesis. The molecular mechanisms and extracellular signaling factors that regulate this process remain to be fully elucidated. The current study investigates the mechanisms utilized by anti-Mü llerian hormone (AMH; i.e. Mü llerian inhibitory substance) to inhibit the primordial to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 102 publications
8
102
2
5
Order By: Relevance
“…Conservation of the ovarian reserve after injection of recombinant AMH into young mice has also been observed (Hayes et al 2016). Exogenous application of AMH inhibits primordial follicle activation in explant cultures of human, rat, mouse and goat ovary tissue (Durlinger et al 2002, Gigli et al 2005, Carlsson et al 2006, Nilsson et al 2007, Rocha et al 2016. Similar experiments have shown that positive regulators of primordial follicle activation such as KIT-ligand, fibroblast growth factor 2, 7 or gremlin antagonise the effects of AMH (Nilsson et al 2007.…”
Section: :1mentioning
confidence: 76%
“…Conservation of the ovarian reserve after injection of recombinant AMH into young mice has also been observed (Hayes et al 2016). Exogenous application of AMH inhibits primordial follicle activation in explant cultures of human, rat, mouse and goat ovary tissue (Durlinger et al 2002, Gigli et al 2005, Carlsson et al 2006, Nilsson et al 2007, Rocha et al 2016. Similar experiments have shown that positive regulators of primordial follicle activation such as KIT-ligand, fibroblast growth factor 2, 7 or gremlin antagonise the effects of AMH (Nilsson et al 2007.…”
Section: :1mentioning
confidence: 76%
“…S2A). Reports of the effect of MIS on follicles have been mixed, with some studies suggesting an activating effect (45,46) and others implying a direct inhibitory effect (18,47), indirect inhibition via gonadotropins (48,49), or even regulation of meiosis (50). In past studies, the magnitude of inhibition of primordial follicle recruitment in vivo and in vitro has been perceived as relatively modest because of difficulties in achieving high concentrations of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when ovaries from Misr2-knockout mice are implanted in the chicken embryos, the primordial follicles are recruited at a high rate, equivalent to wild-type ovaries implanted in gonadectomized chicks with no MIS (17). Similarly, in ovarian cultures from postnatal day 4 rats, a stage at which only primordial follicles are present, 50 ng/mL MIS was sufficient to inhibit, albeit modestly, the transition of primordial to primary follicles compared with controls (18).…”
mentioning
confidence: 92%
“…Several growth factors have been identified that regulate primordial to primary follicle transition by paracrine and autocrine signaling pathways including: kit ligand (KL); leukemia inhibitory factor (LIF); bone morphogenetic protein 4 (BMP4); BMP7; platelet-derived growth factor (PDGF); basic fibroblast growth factor (bFGF); and glial-derived neurotrophic factor (GDNF; Fortune 2003, Skinner 2005, Visser & Themmen 2005, Dole et al 2008. Anti-Müllerian hormone/Müllerian inhibitory substance and stromal-derived factor-1 (SDF-1/ CXCL12) inhibit primordial to primary follicle transition (Ikeda et al 2002, Holt et al 2006, Nilsson et al 2007. Once the supply of follicles in the ovary is exhausted reproduction ceases and, in humans, women enter menopause (Gosden et al 1983, Richardson et al 1987, Faddy 2000.…”
Section: Introductionmentioning
confidence: 99%